2020
DOI: 10.1155/2020/2462039
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Two Safflower Derived Compounds, Kaempferol and Hydroxysafflor Yellow A, on Hyperglycaemic Stress-Induced Podocyte Apoptosis via Modulating of Macrophage M1/M2 Polarization

Abstract: Objective. The primary initiating mechanism in diabetes nephropathy (DN) is hyperglycemia-induced inflammation in which macrophage and podocyte play important roles. The present research is aimed at exploring the effects of kaempferol (Ka) and hydroxysafflor yellow A (HSYA) on classically activated (M1)/alternatively activated (M2) macrophage polarization and podocyte apoptosis under hyperglycaemic conditions in vitro. Methods. (1) RAW264.7 cells were treated with 11.1 mM glucose (NG), 33.3 mM glucose (HG), Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…MPC-5 cell line is also widely used to evaluate renal injury in vitro [ 23 ]. Related research showed that HG-induced apoptosis of podocytes and pancreatic β -cells was reversed by HSYA [ 14 , 18 ].…”
Section: Antidiabetic Pharmacological Research and Related Mechanismsmentioning
confidence: 99%
See 4 more Smart Citations
“…MPC-5 cell line is also widely used to evaluate renal injury in vitro [ 23 ]. Related research showed that HG-induced apoptosis of podocytes and pancreatic β -cells was reversed by HSYA [ 14 , 18 ].…”
Section: Antidiabetic Pharmacological Research and Related Mechanismsmentioning
confidence: 99%
“…For both diabetic wounds and DN progression, a central feature is the persistence of chronic inflammation, which is partly due to the prolonged presence of proinflammatory macrophages [ 25 , 26 ]. In HG- and lipopolysaccharide- (LPS-) induced RAW264.7 macrophage cells, HSYA showed its anti-inflammatory effects by decreasing TNF- α , IL-1 β , and nitric oxide (NO) levels [ 14 , 17 ]. From Table 1 , we could see that the main antidiabetic mechanism of HSYA is through its anti-inflammatory activity.…”
Section: Antidiabetic Pharmacological Research and Related Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations